2016
DOI: 10.1007/s00330-016-4671-1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasound visualization of the recurrent motor branch of the median nerve: normal and first pathological findings

Abstract: PurposeTo evaluate in a prospective study the possibility of visualization and diagnostic assessment of the recurrent motor branch (RMB) of the median nerve with high-resolution ultrasound (HRUS).Materials and methodsHRUS with high-frequency probes (18–22 MhZ) was used to locate the RMB in eight fresh cadaveric hands. To verify correct identification, ink-marking and consecutive dissection were performed. Measurement of the RMB maximum transverse-diameter, an evaluation of the origin from the median nerve and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(53 reference statements)
2
17
0
Order By: Relevance
“…Several studies have recently demonstrated the interest of ultrasound-guided transection of the retinaculum. [2][3][4][5][6][7] This technique has the advantages of (1) great safety, due to continuous ultrasound monitoring and visualization of variants of the median nerve, [8][9][10] and (2) a decrease in size of the incision, enabling a more rapid return to work and a more aesthetic scar. 6,11 Percutaneous access by ultrasound-guided surgery (UCTR) is, at least, 10 times smaller than with classical surgical techniques.…”
Section: Ultrasound-guided Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recently demonstrated the interest of ultrasound-guided transection of the retinaculum. [2][3][4][5][6][7] This technique has the advantages of (1) great safety, due to continuous ultrasound monitoring and visualization of variants of the median nerve, [8][9][10] and (2) a decrease in size of the incision, enabling a more rapid return to work and a more aesthetic scar. 6,11 Percutaneous access by ultrasound-guided surgery (UCTR) is, at least, 10 times smaller than with classical surgical techniques.…”
Section: Ultrasound-guided Surgerymentioning
confidence: 99%
“…Ultrasound assessment of a transligament pathway at risk of iatrogenic injury during transection of the retinaculum 15 is a clear advantage of UCTR. 9,10 The position of the vascular arch is located. Finally, location of a safe zone between the ulnar artery and the median nerve enables visualization of the virtual path of the surgical instruments.…”
Section: Preoperative Consultationmentioning
confidence: 99%
“…The small motor branch of the median nerve arises at the level of the carpal tunnel and provides innervation to the muscles of the thenar eminence. Its US appearance has been recently described . Due to its variable origin, the nerve can be injured during a carpal tunnel release.…”
Section: Pathologic Us Findingsmentioning
confidence: 99%
“…Its US appearance has been recently described. [37][38][39] Due to its variable origin, the nerve can be injured during a carpal tunnel Figure 19. Complete section of the radial collateral nerve of the thumb after surgical treatment of trigger thumb syndrome.…”
Section: After Surgerymentioning
confidence: 99%
“…Beyond cadaveric studies and operative validation of these variants, new technologies have helped clinicians and surgeons better visualize and characterize these anomalies with the use of high-resolution ultrasound, magnetic resonance imaging, and operative technologies. 3 , 4 An example of an operative technology improvement is the STRATOS endoscopic CTR system (STRATOS, A.M. Surgical, Smithtown, N.Y.). This system provides a clear cannula that aids with visualization of the entire carpal tunnel ( see figure, Supplemental Digital Content 1 , which displays the STRATOS ECTR system with clear cannula and independent blade, http://links.lww.com/PRSGO/A528 ).…”
mentioning
confidence: 99%